Profiles of executive function in parents and siblings of individuals with autism spectrum disorders - Wong, D; Maybery, M; Bishop, D; Maley, A; Hallmayer, J (Blackwell Munksgaard, 2006)
Delineation of a cognitive endophenotype for autism is useful both for exploring the genetic mechanisms underlying the disorder and for identifying which cognitive traits may be primary to it. This study investigated whether first-degree relatives of individuals with autism spectrum disorders (ASDs) demonstrate a specific profile of performance on a range of components of executive function (EF), to determine whether EF deficits represent possible endophenotypes for autism. Parents and siblings of ASD and control probands were tested on EF tasks measuring planning, set-shifting, inhibition and generativity. ASD parents showed poorer performance than control parents on a test of ideational fluency or generativity, and ASD fathers demonstrated a weakness in set-shifting to a previously irrelevant dimension. ASD siblings revealed a mild reduction in ideational fluency and a weakness in non-verbal generativity when compared with control siblings. Neither ASD parents nor siblings displayed significant difficulties with planning or inhibition. These results indicated that the broad autism phenotype may not be characterized primarily by impairments in planning and cognitive flexibility, as had been previously proposed. Weaknesses in generativity emerged as stronger potential endophenotypes in this study, suggesting that this aspect of EF should play a central role in cognitive theories of autism. However, discrepancies in the EF profile demonstrated by parents and siblings suggest that factors related to age or parental responsibility may affect the precise pattern of deficits observed.